2002
DOI: 10.1183/09031936.02.00208202
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between airway responsiveness to methacholine and responsiveness to antigen

Abstract: Dissociation between airway responsiveness to methacholine and responsiveness to antigen. A. Kamachi, Y. Nasuhara, M. Nishimura, T. Takahashi, Y. Homma, Y. Ohtsuka, M. Munakata. #ERS Journals Ltd 2002. ABSTRACT: Repeated aerosolized antigen challenges to brown Norway (BN) rats generate nonspecific airway hyperresponsiveness (AHR). On the other hand, some studies have demonstrated that repeated antigen challenge could attenuate antigenspecific AHR in BN rats. The authors questioned whether such dissociation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This is in agreement with studies showing the enhanced bronchoconstrictor responses to methacholine in rodent models of allergic asthma [13,14]. We have chosen ELGV method since it is a rapid, quantitative, sensitive and reproducible technique that does not interfere with other experimental results.…”
Section: Discussionsupporting
confidence: 63%
“…This is in agreement with studies showing the enhanced bronchoconstrictor responses to methacholine in rodent models of allergic asthma [13,14]. We have chosen ELGV method since it is a rapid, quantitative, sensitive and reproducible technique that does not interfere with other experimental results.…”
Section: Discussionsupporting
confidence: 63%
“…The earlier results relating to the effects of inhaled allergen are far more controversial. Some authors reported no effects of a single inhalation of OVA on the lung responsiveness [35,37], while others provided evidence of the development of BHR and lung inflammation following a single exposure to an aerosol of various allergens [33,34,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ragweed and grass pollen extracts induce stronger stimuli to the immune system than does OVA [33]. Furthermore, lung inflammation and BHR have been provoked by a single OVA aerosol in highly inbred Brown-Norway rats [34,38]. Since genetic differences influence the expression of a complex immune disease [54,55], it seems plausible that the Wistar rats used in the present study do not develop a detectable BHR or airway inflammation after a single OVA inhalation in contrast with a more susceptible immune system in Brown-Norway rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations